การพัฒนาโปรแกรมการศึกษานอกระบบโรงเรียน ตามแนวคิดการเรียนรู้แบบร่วมกัน เพื่อพัฒนาทักษะการแก้ปัญหาของเด็กเร่ร่อน - สารีพันธุ์ ศุภวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study and develop a program based on collaborative learning approach for the development of problem solving skills for the street children who live in Bangkok Metropolis. The samples were thirty-two street children. They were assigned into two groups: an experimental group and a control group, each group consisted of sixteen people. The research methodology was a quasi-experimental design. The research procedures were to 1. study the street children s problems and their problem solving methods, 2 develop a non-formal education program. 3. validated the program and 4. implement the programs. The instruments were a pretest- posttest as well as the questionnaires. The research results were as follows 1. The street children s problems were the illness, and lacking of self-confidence. Their problem solving methods were unsystematic. 2. The program s elements consisted of the objectives, the target group, the instructors, models of learning, the contents, the activities, the instructional media, and the program evaluation. 3. The results from the implementation of program were as follows 3.1 before using the programs, the average scores of an experimental group and a control group were not different. 3.2 after using the programs, the average scores of an experimental group were more increased than a control group with a statistical significant difference at the .05 level. 3.3 after using the programs, the average scores of an experimental group were increased with a statistical significant difference at the .05 level. 3.4 after using the programs, the collaborative learning behaviors of an experimental group was increased. 5. The factors effecting the program were the street children s roles, the instructor s roles, timing and the learning environment